Low-Density Neutrophils in Healthy Individuals Display a Mature Primed Phenotype - Blanco-Camarillo, Carlos; Alemán, Omar Rafael; Rosales, Carlos (Frontiers in Immunology, 2021)
Neutrophils are the most abundant leukocytes in human peripheral blood, comprising about 70 % of all leukocytes. They are regarded as the first line of defense of the innate immune system, but neutrophils have also the ability of regulating the adaptive immune response. Recently, However, multiple phenotypes and functional states of neutrophils have been reported, particularly in inflammation, autoimmunity, and cancer. One possible subtype of neutrophils, the so-called low-density neutrophils (LDN) is found among mononuclear cells (MNC), monocytes and lymphocytes, after separating the leukocytes from blood by density gradient centrifugation. LDN increase in numbers during several pathological conditions. However, LDN present in healthy conditions have not been investigated further. Therefore, in order to confirm the presence of LDN in blood of healthy individuals and to explore some of their cellular functions, neutrophils and MNC were isolated by density gradient centrifugation. Purified neutrophils were further characterized by multicolor flow cytometry (FACS) and then, using the same FACS parameters cells in the MNC fraction were analyzed. Within the MNC, LDN were consistently found. These LDN had a normal mature neutrophil morphology and displayed a CD10+, CD11b+, CD14low, CD15high, CD16bhigh, CD62L+, CD66b+, and CXCR4+ phenotype. These LDN had an enhanced reactive oxygen species (ROS) production and increased phagocytic capacity and were able to produce neutrophil extracellular traps (NET) similarly to neutrophils. These data confirm the presence of a small number of LDN is blood of healthy individuals and suggest that these LDN represent mature cells with a primed phenotype.